2016
DOI: 10.1111/cyt.12399
|View full text |Cite
|
Sign up to set email alerts
|

Cytological features of solid variants of papillary thyroid carcinoma: a fine needle aspiration cytology study of 18 cases

Abstract: Solid clusters and small papillary clusters in conjunction with a clean background are diagnostic clues that indicate SV-PTC cytologically. It is thought that small papillary clusters reflect the micropapillary growth pattern seen within the lumen of middle-sized follicular structures. The presence of nuclear findings typical of conventional PTC and the absence of mitotic figures and necrotic materials are important for distinguishing SV-PTC from poorly differentiated carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 12 publications
1
27
1
Order By: Relevance
“…Although we found nuclear elongation in most (89%) of our cases, Baloch et al [24] reported nuclei in SVPTC to be more rounded than oval. INIs were found in 67% of the cases in the current study, not very different from the results reported by Higuchi et al [12] (78%) and Ohashi et al [18] (65%). INIs, as expected, were also seen in most (83%) of cPTCs.…”
Section: Discussioncontrasting
confidence: 87%
See 3 more Smart Citations
“…Although we found nuclear elongation in most (89%) of our cases, Baloch et al [24] reported nuclei in SVPTC to be more rounded than oval. INIs were found in 67% of the cases in the current study, not very different from the results reported by Higuchi et al [12] (78%) and Ohashi et al [18] (65%). INIs, as expected, were also seen in most (83%) of cPTCs.…”
Section: Discussioncontrasting
confidence: 87%
“…Only 3 studies detailing cytological features of this rare variant have been published [7, 12, 18]; the rest are case reports or lack detailed description [4, 5, 19-22]. We retrospectively evaluated aspiration smears of 9 SVPTC cases we came across over a period of 3 years and compared their various cytomorphological features with those of NIFTP/FVPTC, cPTC, and PDTC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The SV is a rare variant of PTC (≤3%) that is still poorly characterized and for which there are conflicting reports about its behavior . It is more common in children and in the Chernobyl nuclear incident survivors (in whom up to 34% of PTCs are SVs).…”
Section: Solid Variantmentioning
confidence: 99%